2014
DOI: 10.1021/la4042088
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Aspects of Lipase B from Candida antarctica in Bicontinuous Microemulsions

Abstract: Biotechnology involves applying enzymes in organic synthesis to convert non-natural substrates into enantiomerically pure products under mild reaction conditions. Non-natural substrates are often lipophilic molecules that can hardly be accessed and converted by enzymes in their natural aqueous environment. Bicontinuous microemulsions provide a spongelike nanostructure with a large interfacial area between aqueous and oil domains, which makes them valuable alternative reaction media. In the present study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…LipA was targeted in these studies because it is an industrially important enzyme that is used in esterificationa nd transesterification reactions, as well as am odel enzyme for understanding the effects of ILs on enzyme structure. [11][12][13][14][15][16] To understand the molecular basis for the improved stability of QM-lipAa swell as, more generally,the nature of the interaction of ILs with enzymes, we determined the crystal structures of wild-type lipA and QM-lipA in the presenceo fI Ls. Specifically,t he structureso fw ild-type lipA and QM-lipA were solved by soakingc rystals of each enzyme in aqueous solutions with different concentrationsof[ BMIM] [Cl].O fs pecific interest was determining the location and binding modeso ft he cation and anion of the IL in each structure.…”
mentioning
confidence: 99%
“…LipA was targeted in these studies because it is an industrially important enzyme that is used in esterificationa nd transesterification reactions, as well as am odel enzyme for understanding the effects of ILs on enzyme structure. [11][12][13][14][15][16] To understand the molecular basis for the improved stability of QM-lipAa swell as, more generally,the nature of the interaction of ILs with enzymes, we determined the crystal structures of wild-type lipA and QM-lipA in the presenceo fI Ls. Specifically,t he structureso fw ild-type lipA and QM-lipA were solved by soakingc rystals of each enzyme in aqueous solutions with different concentrationsof[ BMIM] [Cl].O fs pecific interest was determining the location and binding modeso ft he cation and anion of the IL in each structure.…”
mentioning
confidence: 99%
“…This allows counteracting and thus preventing any changes of the phase behaviour, that is, of the microstructure, during the reaction. The influence of CalB on the phase behaviour of the microemulsion system H 2 O/NaCl (CalB)– n ‐octane–C 10 E 5 was published previously and showed that an increase of CalB concentration in the microemulsion system shifts the phase inversion temperature T̃ to lower values and that $\tilde \gamma $ passes a minimum with increasing CalB concentration 16. The phase behaviour of the CalB‐containing microemulsions combined with the partitioning studies revealed that 80–90 % of the CalB molecules are located at the interfacial layer, whereas the rest is located in the water domain of the microemulsion 16.…”
Section: Resultsmentioning
confidence: 93%
“…The influence of CalB on the phase behaviour of the microemulsion system H 2 O/NaCl (CalB)-n-octane-C 10 E 5 was published previously and showed that an increase of CalB concentration in the microemulsion system shifts the phase inversion temperature T to lower values and that g passes a minimum with increasing CalB concentration. [16] The phase behaviour of the CalB-containing microemulsions combined with the partitioning studies revealed that 80-90 % of the CalB molecules are located at the interfacial layer, whereas the rest is located in the water domain of the microemulsion. [16] In the following, the influence of one substrate and two products on the phase behaviour of microemulsions containing buffer/4 wt % NaCl/p-nitrophenol-n-octane/p-nitrophenyl palmitate/palmitic acid-C 10 E 5 is presented.…”
Section: Phase Behaviour Of Microemulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Additionally, the high internal surface of microemulsions mimics the situation at the cell membrane and thus proved to be beneficial for the performance of enzymatic reactions. [9,10] The high solubility of a great variety of compounds in ILs widens the scope for, and gives access to, applications that are not possible with conventional H 2 O -oil microemulsions. So far successful examples of H 2 O -IL microemulsions as reaction media have been found for lactase catalysed reactions [11] and for the preparation of starch nano-particles [12] or porous nano-rods.…”
Section: Introductionmentioning
confidence: 99%